Soft Systems Methodology for the transdisciplinary study of Communication Systems - Murillo Sandoval, Sandra Leticia; Badillo-Piña, Isaías; Peón-Escalante, Ignacio Enrique (Acta Universitaria, 2019)
The aim of this paper is to present an outline of research results about communication systems, under a cybernetic approach. Cybernetics integrates and organizes fundamental principles and processes in the study of the communication under a transdisciplinary point of view. Second-order systemic and cybernetic methodologies such as the Soft System Methodology (Checkland & Poulter, 2010) organized ontological and epistemological knowledge about communication in a conceptual or practical way. The approach come from a broader research project on communication as a holodynamic or evolutionary system. It contributes to understand and to aim new stages of knowledge for the study of communication systems. The study puts forward the idea of communication as an increasingly integrated system with more applications in real world.